Distribución geográfica de Boa Constrictor Occidentalis Linnaeus, 1758 (Serpentes: Boidae) - Acosta, Juan Carlos (2001)
Distribución geográfica de Boa Constrictor Occidentalis Linnaeus, 1758 (Serpentes: Boidae).